Is(Are) There a New Right(s) in Chile? - Bustamante Olguín, Fabián (2023)
The purpose of this article is to make a contingent theoretical reflection on whether the "new right" that is emerging is radical or simply a continuation of the chicago gremialista right that has been hegemonic in recent years in the recent political history of Chile. To discuss the limits of rights, their particularities and analytical aspects, a specialized bibliography on rights in Chile and abroad is used. In this article we suggest that the right wing was characterized by ideological hibridation, whose axial characteristic is the co-presence or dialectical integration of a wide range of discourses from different ideological traditions and thought. At the end of this writing, a new possibility of the emergence of a mesocratic and popular nationalist right committed to a national integration based on republican ideals, and a xenophobic radical right, which promotes adherence to values of exclusion in the face of the arrival of immigrants in recent years in Chile.